THE DEVELOPMENT OF BEEKEEPING IN THE REGION AND ITS IMPORTANCE - Qulmurotov Sohibjon Jumaniyozovich (Journal Park Publishing, 2024)
In the article, the demand for beekeeping in the region today and the preservation of its rational specialization in the cultivation of honey and bee products (wax, prapolis, guulchangi (perga), Bee milk and poison), which are its healing products, form the basis of our economy during the transition of our independent republic to a market economy day by day. It is illuminated that the beekeepers of our vilioyat are given a strict task to increase the production of honey and bee products at the expense of increasing the productivity of each bee family.
Keywords: Bee Family, Box Bee, worker bees doing work in the hive, worker bees flying to the field, bee flying to the field, mother Wasp, SUNY released mother Wasp, naturally released mother Wasp, male wasp, honey, pollen, perga, prapolis, wax, bee venom, asalasri milk.